2011
DOI: 10.1093/carcin/bgr304
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-34a inhibits migration and invasion of colon cancer cells via targeting to Fra-1

Abstract: MicroRNA-34a (miR-34a), a transcriptional target of p53, is a well-known tumor suppressor gene. Here, we identified Fra-1 as a new target of miR-34a and demonstrated that miR-34a inhibits Fra-1 expression at both protein and messenger RNA levels. In addition, we found that p53 indirectly regulates Fra-1 expression via a miR-34a-dependant manner in colon cancer cells. Overexpression of miR-34a strongly inhibited colon cancer cell migration and invasion, which can be partially rescued by forced expression of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
101
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(112 citation statements)
references
References 45 publications
9
101
2
Order By: Relevance
“…Overexpression of miR-34a strongly inhibited colon cancer cell migration and invasion, which can be partially rescued by forced expression of the Fra-1 transcript lacking the 3'-UTR. Moreover, they found that miRNA-34a was down-regulated in 25 of 40 (62.5%) colon cancer tissues, as compared to the adjacent normal colon tissues, and that the expression of miRNA-34a was correlated with the DNA binding activity of p53 (160,161). Cheng et al found that circulating miRNA-141 was significantly associated with stage IV colon cancer in a cohort of 102 plasma samples.…”
Section: Biliary Tract Cancer (Btc): Mirna In Body Fluidsmentioning
confidence: 99%
“…Overexpression of miR-34a strongly inhibited colon cancer cell migration and invasion, which can be partially rescued by forced expression of the Fra-1 transcript lacking the 3'-UTR. Moreover, they found that miRNA-34a was down-regulated in 25 of 40 (62.5%) colon cancer tissues, as compared to the adjacent normal colon tissues, and that the expression of miRNA-34a was correlated with the DNA binding activity of p53 (160,161). Cheng et al found that circulating miRNA-141 was significantly associated with stage IV colon cancer in a cohort of 102 plasma samples.…”
Section: Biliary Tract Cancer (Btc): Mirna In Body Fluidsmentioning
confidence: 99%
“…miR-34a was found present at highest levels in the brain, and miR-34b/c was most highly expressed in the lung (Bommer et al, 2007). The miR-34 family members share more than 80% homology and govern similar target genes (Hermeking, 2010), and they can act (Tazawa et al, 2007;Roy et al, 2012;Wu et al, 2012;Zhang et al, 2014;Akao et al, 2010;Toyota et al, 2008;Ma et al, 2013) as either tumor suppressors or oncogenes depending on the cellular environment in which they are expressed.…”
Section: Discussionmentioning
confidence: 99%
“…MiR-192 and miR-215 are both effectors and regulators of p53 function to suppress colon carcinogenesis [ 160 ]. Another p53 related miRNA, miR-34a, has been shown to inhibit cell invasion in colon cancer cell lines by targeting FRA1 [ 161 ]. Cyclooxygenase 2 (COX-2) can be negatively regulated by miR-101 [ 162 ] and this may contribute to the initiation and progression of colon tumors.…”
Section: Micrornas (Mirnas) In Human Crcmentioning
confidence: 99%